Islamic Counseling Guidance as Teenagers Social Conflict Resolution in Madrasah - Failasufah; Farida Hanum; Mohamad Hilmi Bin Mat Said (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to describe Islamic counseling as a conflict resolution that is packaged strategically as a psychological therapy procedure that can be applied to resolve social conflicts in adolescent students in madrasah. A conflict is a form of interaction between humans who have mutual interests, which can take the form of conflicts, disputes, threats, or anything else to destroy the opponent. The method used in this research is qualitative. The results of the study show that the occurrence of social conflict among adolescent students in madrasahs stems from the emergence of several students who number less than one percent of the total number of students in madrasahs who are involved in social groups or gangs acting on behalf of “school gangs” with all of their activities such as freaking out or visiting other schools that are considered enemies, hanging out at food stalls, fighting with peers, and convoying on the streets. This was done because of the interests of the social group of young students to show the existence and identity of their group. Efforts to prevent and resolve these problems through Islamic guidance and counseling services as a conflict resolution that aims to assist teenage students in solving conflict problems in peaceful ways.